Attrition Across the HIV Cascade of Care Among a Diverse Cohort of Women Living With HIV in Canada. (1st October 2018) - Kerkerian, Geneviève; Kestler, Mary; Carter, Allison; Wang, Lu; Kronfli, Nadine; Sereda, Paul; Roth, Eric; Milloy, M-J; Pick, Neora; Money, Deborah; Webster, Kath; Hogg, Robert S.; et al.
Abstract : Background: In North America, women have lower engagement across the HIV cascade of care compared with men. Among women living with HIV (WLWH) in Canada, we measured the prevalence and correlates of attrition across cascade stages overall, and by key subpopulations. Methods: We analyzed baseline survey data regarding 6 nested stages of the HIV cascade among 1424 WLWH enrolled in the Canadian HIV Sexual and Reproductive Health Cohort Study (CHIWOS), including: linked to care, retained in care, initiated antiretroviral therapy (ART), current ART use, ART adherence (≥90%), and viral suppression (<50 copies/mL). Logistic regression identified factors associated with attrition at each stage. Results: Overall, 98% of WLWH were linked to care; 96% retained; 88% initiated ART; 83% were currently on ART; and, among those on ART, 68% were adherent and 72% were virally suppressed, with substantial variability by subpopulation (49%–84%). The largest attrition occurred between current ART use and adherence (−17%), with the greatest losses among indigenous women (−25%), women who use illicit drugs (−32%), and women incarcerated in the past year (−45%). Substantial attrition also occurred between linkage to care and ART initiation (−11%), with the greatest losses among women 16–29 years (−20%) and with unstable housing (−27%). Factors independently associated with attrition at viral suppression included household annual income, racial discrimination, incarceration history, age, and resilience. Conclusions: Overall, 28% of WLWH were lost across the HIV care cascade, with significant differences by stage, subpopulation, and social inequities. Targeted interventions are needed to improve women's retention across the cascade.